The integrated multi-omics analysis unravels distinct roles of Malvaceae-derived protein hydrolysate and its molecular fraction in modulating tomato resilience under limited nitrogen availability - Sonia Monterisi; Monica Yorlady Alzate Zuluaga; Biancamaria Senizza; Mariateresa Cardarelli; Youssef Rouphael; Giuseppe Colla; Luigi Lucini; Stefano Cesco; Youry Pii (Plant Stress)
Nitrogen (N) is essential for plant growth, yet its limited availability challenges crop development. Protein hydrolysates (PHs) from plant sources are biostimulants that can enhance nutrient use efficiency and stress tolerance in crops, although their mode of action, depending on the botanical origin and the molecular fraction, is largely unknown. This study investigated the molecular effects of a Malvaceae-based pH (C) and its medium molecular weight fraction (F2) on tomato plants under optimal and suboptimal N conditions. Plants were foliarly-treated with C, F2, or left untreated, and analysed using integrated omics techniques. Under optimal N conditions, C upregulated genes associated with photosynthesis, aging, and abiotic stress responses, suggesting enhanced metabolism and resilience. Both C and F2 modulated genes involved in hormone signalling, particularly auxin and cytokinin, and Circadian rhythm pathways. Under suboptimal N, C influenced hormone signalling and light response genes, potentially alleviating N deficiency stress. Metabolomic analysis showed that under low N, C increased fatty acids, amino acids, and phenolic compounds linked to stress protection, while F2 had a milder effect. Multi-omics analysis showed that C impacted N metabolism upregulating nitrate transporters (NRT1) and promoting metabolic reprogramming, whereas F2 primarily influenced hormonal signalling and Circadian rhythm. Overall, C might be more effective than F2 in optimizing N use efficiency. Our study demonstrates that Malvaceae-based PHs can modulate gene expression and metabolism in tomato plants under suboptimal N level, enhancing adaptation to N shortage. However, further research is needed to elucidate the mode of action of PHs in N metabolism.